POST BREXIT: FRENCH MEDIA’S VIEWS ON THE BRITISH MONARCHY - Ghefira, Prazna Alyfia; Laksman-Huntley, Myrna (UI Scholars Hub, 2025)
The Brexit referendum has stimulated European media to highlight the impact for Britain and other European Union countries. As a country established with two different political ideologies, French media has the ability to cover the latest global issues from the point of view of their political ideology. This research aims to see whether the French media shows a negative framing towards Britain and maintains the media ideology, right (Le Figaro) and center-left (Le Monde), in publicizing the news of the death of Queen Elizabeth II and the cancer diagnosis of King Charles III. This qualitative research uses the Creswell (2014) method, syntactic theory by Le Querler (1994), and media framing by Pan & Kosicki (1993). The research found that there is no negative sentiment from French media towards Britain. However, Le Figaro’s coverage reflects a negative framing towards the news of Charles III's current health. This is evidenced through the usage of simple sentences (les phrases simples) with a direct approach in Le Figaro’s headlines to give the impression of its focus to the continuation of the monarchy. By contrast, Le Monde’s coverage tends to use compound sentences (les phrases complexes) in the headlines with a descriptive content that focuses on the reader’s emotions. The dismantling script and rhetorical structure of news media framing by Pan & Kosicki (1993) are the essential elements of this research to identify how the French media frames news regarding two leaders of the British monarchy.